2018
DOI: 10.1212/cpj.0000000000000451
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors associated with Guillain-Barré syndrome following surgery

Abstract: Surgery antedated GBS in 9.1% of patients. Postsurgical GBS was more common in patients with an active malignancy. A prospective study is needed to determine whether active malignancy represents an independent risk factor for the development of postsurgical GBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 24 publications
4
35
1
Order By: Relevance
“…1 Other preceding immunogenic events or conditions, including immunisation, malignancy and pregnancy, observed occasionally, have a less clear relationship to GBS pathogenesis. 8,[18][19][20] Recurrent GBS occurred rarely, in keeping with previous reports. 21 AIDP was most common, consistent with studies in primarily Caucasian cohorts in which demyelinating forms predominate.…”
Section: Discussionsupporting
confidence: 90%
“…1 Other preceding immunogenic events or conditions, including immunisation, malignancy and pregnancy, observed occasionally, have a less clear relationship to GBS pathogenesis. 8,[18][19][20] Recurrent GBS occurred rarely, in keeping with previous reports. 21 AIDP was most common, consistent with studies in primarily Caucasian cohorts in which demyelinating forms predominate.…”
Section: Discussionsupporting
confidence: 90%
“…12 Another large consecutive series study showed postsurgical GBS was more common in patients with preexisting autoimmune disorders or active malignancies. 13 However, neither autoimmune diseases nor malignancies were found in this study. Prospective studies are still needed to determine whether autoimmune disorder and active malignancy can increase the risk of post-surgical GBS.…”
Section: Discussioncontrasting
confidence: 57%
“…Ninety-four studies involved a total of 136 patients diagnosed with GBS associated with trauma-related triggers, including injury, surgery, intracranial hemorrhage, and heatstroke, which were subjected to analysis ( Table 1). Six case series (15,(110)(111)(112)(113)(114) including trauma-related GBS patients with aggregated data were reviewed and generalized ( Table 2). Figure 1 shows the PRISMA flow diagram of the selection procedure of included studies.…”
Section: Resultsmentioning
confidence: 99%